BUDIDAYA UDANG WINDU, Penaeus monodon PADA TAMBAK TANAH SULFAT MASAM DI TARAKAN, KALIMANTAN TIMUR - Brata Pantjara; Markus Mangampa; Rachman Syah (Jurnal Perikanan Universitas Gadjah Mada, 2010)
Low productivity in acid sulphate soil (ASS) pond can be improved by pond bottom reclamation. The aim of this research was to observe the effects of soil reclamation in acid sulphate soil on survival rate and production of tiger prawn. The research was conducted in a farmer pond in West Tarakan, Tarakan, East Kalimantan. The soil treatments were reclamation and without reclamation. The density of tiger prawn was 40.000 ind./ha during 3 months. The result showed that ponds with and without reclamation produce survival rate by 28.5% and 21.6% respectively. Pond with reclamation produce higher tiger prawn production (191.9 kg/ha) than without reclamation (143 kg/ha).